Upaya Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa dengan Menggunakan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) pada Kelas VIII SMP Bhakti Nusantara Jakarta: Upaya Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa dengan Menggunakan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) pada Kelas VIII SMP Bhakti Nusantara Jakarta - Astuti, Nur Meilani (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2020)
This research is class action research aimed at enhancing the students understanding mathematical concepts using NHT cooperative learning model in class VIII-1 SMP Bhakti Nusantara Jakarta. The study was implemented in 3 cycles. The NHT cooperative learning model consists of five phases, they are: Numbering phase, questioning phase, heads together phase, call out phase and answering phase. The final test score for understanding the mathematical concepts of SP1 in cycle I was 78.6, in cycle II became to 82.1, in cycle III increased to 85.7. SP2 in cycle I was 71,4, in cycle II became to 75, in cycle III increased to 92,9. SP3 in cycle I was 57,1, in cycle II became to 67,9, in cycle III increased to 75. SP4 in cycle I was 67,9, in cycle II became to 78,6, in cycle III increased to 82,1. SP5 in cycle I was 46,4, in cycle II became to 71,4, in cycle III increased to 85,7. SP6 in cycle I was 57,1, in cycle II became to 60,8, in cycle III increased to 75. So, it can be concluded that the application of the NHT cooperative model can increase the student’s ability in understanding mathematical concepts.